(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Heritage tourism involves service to tourists with the uniqueness of nature, quality, and according to him comfortability and heritage features. Cultural, traditional, natural & and educational facilities are the important features of heritage tourism places. A significant difference between the comfortability or the expectation of tourists between services offered in place of heritage tourism. Heritage tourism environment, weather, art, painting, cultural rules, and traditions attract More no domestic tourists in that place. The government arranged various cultural, traditional, and local event programs and gave traditional hospitality facilities for the development of the heritage tourism place of Bastar. The tourism department focuses on improving infrastructure quality and renewing it, the availability of document factsheet related to heritage places in all tourism organizations. Now that time tourism is one of the high revenue generators and contributors to GDP. [source: Dubey et al. (2021)]